EKSISTENSI KANAL YOUTUBE RIRI CERITA ANAK INTERAKTIF DALAM MENERAPKAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR - Rara, Shaflyra Ramadhaniar Ardahlia; Ezik Firman Syah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the era of globalization, technological advances provide great opportunities to utilize audiovisual media as effective teaching materials. The YouTube channel "Riri Sekolah Anak Interactive," produced by Educa Studio, offers interactive animated content that combines entertainment with character education values. This research aims to identify the character education values contained in the channel's content and describe its role in supporting student character formation. The method used in this research is a qualitative descriptive approach using content analysis data collection techniques, in the form of observation and documentation. Checking the validity of this research data uses source triangulation. Data were analyzed through the steps of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the religious character aspect has 6 points, honesty has 8 points, tolerance has 3 points, discipline has 5 points, working hard has 7 points, creativity has 2 points, independence has 4 points, democratic sense has 1 point, curiosity has 2 points, national spirit has 2 points. , love of the country 2 values, respect for achievements 3 values, communicative 5 values, love of peace 3 values, care for the environment 2 values, care for the social environment 6 values, responsibility 8 values. The obstacles in this research are limited teaching materials, not all classes are facilitated with projectors to increase the use of audio-visual media.